Pola Konsumsi Teh di Desa Melikan, Kecamatan Rongkop, Kabupaten Gunung Kidul - Kusumawati, Maya; Cahyono, Hendry (Universitas Negeri Surabaya, 2025)
This study aims to understand the tea consumption patterns of the community in Melikan Village, Rongkop District, Gunung Kidul Regency, and to examine the extent to which income influences their choices and frequency of tea consumption. Using a descriptive qualitative approach, data were collected through in-depth interviews and participatory observations involving ten informants selected via snowball sampling. The findings reveal that tea—particularly the Serimpi brand—is an integral part of the community’s social and cultural life, consumed routinely regardless of economic conditions. Consumption frequency ranges from two to four times a day, with diverse preferences in taste and preparation methods. Despite varying income levels, most residents maintain the same consumption habits due to factors such as tradition, personal preference, and social value. These results suggest that tea consumption in Melikan Village is more influenced by established habits and cultural norms than by financial circumstances. The findings align with the concept of autonomous consumption and partially reflect Engel’s Law.